ANALISIS PERAN MEDIA SOSIAL DALAM PENGARUH POLITIK MENJELANG PEMILU : ANALISIS PERAN MEDIA SOSIAL DALAM PENGARUH POLITIK MENJELANG PEMILU - vivifriskilangela. (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2023)
The purpose of this research is analysis of the role of social media in political influence ahead of the election. The method used in this research is literature review. Data collection techniques are documented from journals on Google Schoolar. Data analysis technique with critical review. research results Social media plays a central role in disseminating political information to the wider community. In the context of elections, social media enables candidates and political parties to directly communicate with potential voters, spread their political platforms, and provide a better understanding of their visions and plans.